Learning from nature: experimental observation of Mimosa Pudica (A) - See Toh, Hong Jun (Nanyang Technological University, 2024)
Mimosa pudica, commonly known as the sensitive plant, is frequently found in Singapore. When stimulated, it exhibits a unique defense mechanism by folding its leaves inwards and drooping downwards. This behavior demonstrates that plants, like animals, possess reflexes to respond to potential threats. However, unlike animals, plants lack neurons and muscles to facilitate these reflexes. This report investigates how Mimosa pudica achieves an immediate response to external stimuli without these conventional reflex components. The study aims to examine whether the constant wind stimuli affects the Mimosa pudica’s closing time, recovery time, and drop angle. We will analyze the correlations between these variables and investigate the plant's fatigue effects. Our methodology involves collecting data from a sample of 50 home-grown Mimosa pudica plants using wind stimuli. We will record and compare the closing time, recovery time, and drop angle for each specimen. A comprehensive statistical analysis will be conducted, including the creation of normal distribution graphs, box-and-whisker plots and scatterplots. We will calculate means and standard deviations to quantify the observed variations.